Research on the Participation of Chinese Sports Cultural Elite in Ice and Snow Sports - Li, Ping; Liu, Wei (Frontiers in Public Health, 2022)
Governments have a responsibility to provide equal opportunities for sport and physical activity to all people of population. Chinese governments have issued many policies, such as "exhibition in the south, expansion in the West and East" of ice and snow sports to promote and stimulate the participation of the broad masses of the people. As a high-cost sport, the participants of ice and snow sports are usually socially elite groups. This study investigated the participation of cultural elite groups in ice and snow sports and investigated the social mobilization effect of ice and snow sports participation promotion policies by using binary regression and sequential regression models. The research shows that there are two different stages of one-time and continuous participation in the development of ice and snow sports in China. The one-time participation of ordinary people in ice and snow sports is mainly in response to the social mobilization of government policies. At the same time, it is positively correlated with site restrictions and knowledge of ice and snow sports. In the continuous participation group, gender, income, perception of ice and snow culture, and convenience near the site were highly positively correlated with consumption level. According to the results, low- and middle income people are less likely to participate in these activities because of their income. Therefore, this policy can increase inequalities.